Dust and Dignity : Domestic Employment in Contemporary Ecuador - Casanova, Erynn Masi de, 1977- (Book collections on Project MUSE., 2019)
"Through the understudied case of Ecuador, this book separates the exploitation inherent in domestic work from the exploitation that specifically affects migrant women workers"--